2005
DOI: 10.1038/sj.onc.1208597
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor positivity in mammary tumors of Wnt-1 transgenic mice is influenced by collaborating oncogenic mutations

Abstract: The majority (75%) of human breast cancers express estrogen receptor (ER). Although ER-positive tumors usually respond to antiestrogen therapies, 30% of them do not. It is not known what controls the ER status of breast cancers or their responsiveness to antihormone interventions. In this report, we document that transgenic (TG) expression of Wnt-1 in mice induces ER-positive tumors. Loss of Pten or gain of Ras mutations during the evolution of tumors in Wnt-1 TG mice has no effect on the expression of ER, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 72 publications
4
36
1
Order By: Relevance
“…3 and Table S4). This result was unexpected given that genetically engineered mouse models commonly develop ER Ϫ mammary tumors (19). In addition, we observed that all Met mut tumors lacked PR expression.…”
Section: Met Is Highly Expressed In Tumor Cells That Are Pr and Erbb2contrasting
confidence: 49%
“…3 and Table S4). This result was unexpected given that genetically engineered mouse models commonly develop ER Ϫ mammary tumors (19). In addition, we observed that all Met mut tumors lacked PR expression.…”
Section: Met Is Highly Expressed In Tumor Cells That Are Pr and Erbb2contrasting
confidence: 49%
“…The lower-than-expected frequency of engraftment from the Thy1ϩCD24ϩ cells could be due to damage to the cells during isolation that day. Alternatively, the secondary mutations leading to malignant transformation in that particular tumor could have resulted in a tumor whose tumorigenic cells were different from those driving the growth of the other tumors [31]. In six of seven tumors tested, the remaining tumor cells that were not-Thy1ϩCD24ϩCD45Ϫ were significantly depleted of cells capable of forming tumors.…”
Section: Cd24 and Thy1 Tumor Cells Are Enriched For Tumorigenic Cellsmentioning
confidence: 99%
“…Related to this, as MMTV-Wnt-1 tumors are classified as estrogen receptor (ER)-positive [31], and human ERϩ tumors have better prognosis than ERϪ tumors, we were interested to examine the distribution of ERϩ and ERϪ tumors within our two prognostic groups. As expected, the vast majority of the ERϪ patients fell within the worse prognosis group, as did patients with other poor prognostic markers such as basal cell subtype and poor histologic grade (Fig.…”
Section: The Tg/ntg Signature Predicts Survival Of Breast Cancer Patimentioning
confidence: 99%
“…In combination with heterozygosity at the p53 locus, TGFa tumors were ERÀ, consistent with accelerated tumor progression facilitated by genomic instability or selective progression of a distinct tumor precursor subpopulation. Both ER þ and ERÀ tumors have been observed in other mouse models with one or more dysfunctional p53 alleles (Medina and Kittrell, 2003;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%